A chiastic opus to the Creator of “heaven and earth- earth and heaven”: A spatial reading of Psalm 148 and Colossians 1:15-20 - Sutton, L. (Acta Theologica, 2024)
Two hymns that focus on God (and Christ in the New Testament text) as the creator are Psalm 148 and Colossians 1:15-20. In both texts, an interesting chiastic pattern is noticeable concerning A-heaven-B-earth-Bearth-A-heaven. The imagery concerning heaven and earth can be spatially interpreted, as in both these texts, the creation and its inhabitants are understood in relation to, and their position towards God. This article analyses Psalm 148, and then makes a spatial comparison between the Old Testament text of Psalm 148 and the New Testament text of Colossians 1:15-20. The article indicates the importance of the chiastic structure in both of these texts, as it indicates not only a cosmic whole, but also contributes to the interpretive relation of God (and Christ) as creator to the creation and his people.